Feasibility of quaternary ammonium and 1,4-diazabicyclo[2.2.2]octane-functionalized anion-exchange membranes for biohydrogen production in microbial electrolysis cells - Cardeña, René; Žitka, Jan; Koók, László; Bakonyi, Péter; Pavlovec, Lukáš; Otmar, Miroslav; Nemestóthy, Nándor; Buitrón, Germán (Bioelectrochemistry (Amsterdam, Netherlands), 2020)
In this work, two commercialized anion-exchange membranes (AEMs), AMI-7001 and AF49R27, were applied in microbial electrolysis cells (MECs) and compared with a novel AEM (PSEBS CM DBC, functionalized with 1,4-diazabicyclo[2.2.2]octane) to produce biohydrogen. The evaluation regarding the effect of using different AEMs was carried out using simple (acetate) and complex (mixture of acetate, butyrate and propionate to mimic dark fermentation effluent) substrates. The MECs equipped with various AEMs were assessed based on their electrochemical efficiencies, H2 generation capacities and the composition of anodic biofilm communities. pH imbalances, ionic losses and cathodic overpotentials were taken into consideration together with changes to substantial AEM properties (particularly ion-exchange capacity, ionic conductivity, area- and specific resistances) before and after AEMs were applied in the process to describe their potential impact on the behavior of MECs. It was concluded that the MECs which employed the PSEBS CM DBC membrane provided the highest H2 yield and lowest internal losses compared to the two other separators. Therefore, it has the potential to improve MECs.
Keywords: Microbial electrolysis cell; Volatile fatty acids; Geobacter; elektrolýza; membrány umělé; Hydrogen; studie proveditelnosti; Bioelectric Energy Sources; Equipment Design; Internal losses; Anion-exchange membrane; Electrolysis; Biohydrogen; Microbial community analysis; Membranes, Artificial; piperaziny; anionty; design vybavení; vodík; kvartérní amoniové sloučeniny; Quaternary Ammonium Compounds; Piperazines; zdroje bioelektrické energie; Feasibility Studies; Anions